Pengembangan Perangkat Pembelajaran Model Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Hukum Newton - Wahyudi Wahyudi; Susilawati Susilawati; Cindy Bintang Cempaka Putri (Kappa Journal, 2022)
This development research to produce a product in the form of Newton's law learning tools using the Jigsaw Type Cooperative model to improve student learning outcomes that are valid, practical and effective. The research model used is a 4D model consisting of Define, Design, Develop and Disseminate. The products developed are syllabus, Learning Implementation Plans (RPP), Student Worksheets (LKPD) and ability test instruments to improve learning outcomes. The data collection technique used a validation sheet. Product validity was assessed by six validators, analyzed using Content Validy Ratio (CVR) and Content Validity Index (CVI). The product met the criteria very well from presentations by three expert validators and three practitioner validators. The CVI syllabus score reached 0.92 in the very good category, the CVI RPP value reached 0.86 in the very good category, the CVI LKPD score reached 0.85 and the CVI score for learning outcomes reached 0.93. The product meets the practical criteria with a percentage of 88.5% and the product meets the criteria for being quite effective with an N-value of up to 0.62 in the medium category. Based on the interpretation of the data, it is said that Newton's law learning tools use the Jigsaw Type Cooperative model which is valid, practical and effective to improve student learning outcomes.